Pengaruh Disiplin Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Bagian Operasional Pada PT. Bandar Krida Jala (BKJL) Patimban Subang - Andrian, Andrian; Vrans Romi, Mochamad (Lembaga Teewan Journal Solutions, 2026)
This study aims to determine the partial and simultaneous effects of work discipline and work motivation on the performance of operational employees at PT. Bandar Krida Jala (BKJL) Patimban, Subang. The study employs a quantitative method with descriptive and associative approaches. Data were collected through questionnaires, interviews, and documentation involving 60 operational employees and subsequently analyzed using multiple linear regression with the aid of SPSS version 27. The results indicate that work discipline falls into the